MARTYNAS JANKUS AND THE GERMAN REICH - KLEIN, MANFRED (Knygotyra, 2015)
Even today, the name of the Prussian-Lithuanian printer and publicist Martynas Jankus (1858–1946) remains prominent in Lithuanian literature, although the person and his historical role remain unknown to the German public. This article attempts to present aspects of the political situation in the German “Kaiserreich” after 1871 from the Lithuanian perspective. The political situation was influenced by the concept of the national state and the endeavour to establish it as an ethnically and vocally homogeneous German state. Legislation and cultural policy of the united German Reich had substantial effects on the ethnic minority of Prussians-Lithuanians in the then north-eastern East Prussia. The Lithuanian language was particularly affected during the displacement as the taught language from schools. Martynas Jankus, one of the most important voices of Lithuanian ethnic groups, came into conflict with the local authority in East Prussia in the 1880s through his political and publicist activities. What was considered by the Lithuanians as a substantial suppression of the identity and culture of the minority and as a rigid assimilation and Germanisation is partly put into perspective by the fact that a small ethnic group would rather stand on the edge of the attention from the former German minority’s political stance. Much more rigorous legislation and administration intruded into the rights of the much larger – and more politically active – Polish ethnic groups. The Prussians-Lithuanians remained opposed to the political language measures of the Reich until the 1930s, always contradictory and inconsistent. Jankus became associated mainly because of his actual and also alleged connections with the then Russian Lithuania and to activists of the Polish national movement under the scrutiny of the regional authorities. After 1918 he was more closely observed due to his separatist views and activities. In this article, informers’ reports to the German authorities are analysed to establish the importance of the role Jankus played in linking the Lithuanian speaking areas to the young Republic of Lithuania. It shows that he was not considered in any of the examined dossiers to be the most important and, for Germany, the most dangerous personality amongst the protagonists of the national Lithuanian movement.
Keywords: ...